Respuestas
Respuesta dada por:
178
Respuesta:
Explicación paso a paso:
18m4n3 - 6m4n2 + 6 - (24m4n3 +12)=
18m4n3 - 6m4n2 + 6 - 24m4n3 - 12=
-6m4n3 - 6m4n2 - 6=
-6(m4n3 - m4n2 - 1) R//
Saludos.
Respuesta dada por:
19
Respuesta:
18m4n3 - 6m4n2 + 6 - (24m4n3 +12)=
18m4n3 - 6m4n2 + 6 - 24m4n3 - 12=
-6m4n3 - 6m4n2 - 6=
-6(m4n3 - m4n2 - 1) R/
Explicación paso a paso:
D a eso porq viene a ser equivalente entre el m⁴n³- m⁴n²m
Espero te ayude
Preguntas similares
hace 4 años
hace 4 años
hace 7 años
hace 7 años
hace 7 años